Interrelations among scientific fields and their relative influences revealed by an input–output analysis. Issue 1 (February 2016) - Shen, Zhesi; Yang, Liying; Pei, Jiansuo; Li, Menghui; Wu, Chensheng; Bao, Jianzhang; Wei, Tian; Di, Zengru; Rousseau, Ronald; Wu, Jinshan
Abstract : Highlights: We present an approach to measure the influence and interrelation among disciplines. Our approach takes into account both direct and indirect effect. Our method is applicable to all systems described by input–output relations. The approach is applied to the subfields of Physics. The approach is potentially of interest to policy makers and funding agencies. Abstract: In this paper, we try to answer two questions about any given scientific discipline: first, how important is each subfield and second, how does a specific subfield influence other subfields? We modify the well-known open-system Leontief Input–Output Analysis in economics into a closed-system analysis focusing on eigenvalues and eigenvectors and the effects of removing one subfield. We apply this method to the subfields of physics. This analysis has yielded some promising results for identifying important subfields (for example the field of statistical physics has large influence while it is not among the largest subfields) and describing their influences on each other (for example the subfield of mechanical control of atoms is not among the largest subfields cited by quantum mechanics, but our analysis suggests that these fields are strongly connected). This method is potentially applicable to more general systems that have input–output relations among their elements.